Proposals to increase of economics effects of landuse residential end public buildings on the example of Kyiv - Malashevskyi, Mykola; Berova, Polina; Mosiychuk, Yuriy (KNUCA, 2015)
The article considers the current state of land-use in Kyiv. Considerable part of almost all the city's functional areas is used inefficiently. To improve the economic efficiency of their exploitation, we propose an optimizing variant of land-use of residential and public developments by allocation of excess of residential territories. This will provide an opportunity to attract those land plots at auctions to increase revenues to the State and Local Budgets of Ukraine.
Предложения по увеличению экономического эффекта от использования земель жилой и общественной застройки на примере города Киева
Keywords: бурильне обладнання; накопичувач; робочий орган; роздільне обертання; store; boring equipment; working organ